Learning Styles of Undergraduate Medical Students and their Relation with Preferred Teaching-Learning Methods - Karim, Md Rezaul; Talukder, Md Humayun Kabir; Mondol, Rais Uddin; Ghose, Rajesh Kumar; Hossain, Molla Md Iftekhar (TAJ: Journal of Teachers Association, 2023)
This descriptive type of cross-sectional study was conducted to determine the learning styles of undergraduate medical students and their relation with preferred teaching-learning Methods. The study period was from July 2017 to June 2018. The study was carried out among the students of the 2nd, 3rd, and 4th phases of the MBBS course at three government and four nongovernment medical colleges in Bangladesh. Out of seven medical colleges, four were within Dhaka and three outside Dhaka. The sample size was 1004. Medical colleges were selected purposively, and a convenience sampling technique was adopted for data collection. Bangla translated version of Fleming's VARK (visual, auditory, read/write, and kinesthetic) questionnaire was used to identify the learning styles of students. Linear regression was used to compare the VARK learning styles scores with teaching-learning Methods. The study revealed that out of 1004 medical students 64.2% preferred multimodal learning styles, and the rest, 35.8% preferred unimodal learning styles. Among unimodal learning preferences, auditory (A) and kinesthetic (K) were the most preferred sensory modalities of learning. The most preferred teaching Methods among the students were bedside teaching (29.9%), followed by tutorials (25.9%), and practical sessions (20.6%). The most preferred learning method among the students was mixed Methods (60.3%). A positive correlation was present between VARK modes and teaching-learning Methods (P <0.05). Majority of students preferred multimodal learning styles. Students are able to learn effectively as long as the teacher provides a blend of visual, auditory, read/writing, and kinesthetic activities. The study recommended that teachers be aware of the medical students' learning styles and that aligning teaching-learning Methods with learning styles will improve their learning and academic performance. TAJ 2022; 35: No-2: 19-26